Application of the Hadith Study Methodology Hisbah Council of the Persatuan Islam - Siti Mirah Nuraeni; Tajul Arifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Background: The Dewan Hisbah serves as a fatwa and research institution responsible for ensuring that the understanding of Hadith aligns with Sharia principles and can be applied contextually in the lives of Muslims. Purpose of the Study: To understand the methodology of Hadith study implemented by Dewan Hisbah of Persatuan Islam in assessing the authenticity and relevance of Hadith as a basis for issuing fatwas, and to explore the contribution of Dewan Hisbah's application of Hadith study methodology to the development of understanding and implementation of Islamic teachings among Muslims. Methods: The research titled Application of the Hadith Study Methodology of Dewan Hisbah of Persatuan Islam employs a literature review as the primary approach. Literature collection was conducted using two main platforms, PubMed and Google Scholar, with keywords such as